LIVE RECORDINGS. - Eaves, Will (Yale Review, 2015)
The article discusses the adoption of language by people who emigrate early on in life. Topics include speech as a higher brain function resulting from the evolution of the cerebral cortex, human's response to signal transmission, and instinctive deployment of an abandoned human language. A review of Jane Austen's book "Pride & Prejudice" is also given.